Pathological Studies on Acute Marek’s Disease in Native and Crossbred Chickens of Organized Poultry Farm - Makwana, Kinnari R; Joshi, BP; Ghodsara, DJ; Dave, CJ; Patel, Monika P (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The present study was aimed to detect the occurrence of Marek’s disease in a native and cross-bred chickens based on gross and microscopic lesions. Seven different native as well as crossbred strains of poultry flocks were evaluated the mortality pattern based on farm as well as autopsy records and for the gross and microscopic examination of the birds suspected for Marek’s disease. Visceral lymphomas like lesions were recorded in liver, spleen, proventriculus, heart, kidney and gonads. Fragments of the affected organs were collected and placed in 10% formalin for routine histopathology. Under microscopic examination, pleomorphic population of lymphocytes and lymphoblasts were observed. The incidence of MD observed was from 12 to 61 weeks of age with peak mortality from 12 to 31 weeks of age during summer in different strains. The strain wise mortality due to MD ranged between 13.42 (random bred controls) to 36.57% (IWN×Native, F1) with an average of 26.80 %, and it was higher in female than male birds. and indirect contact with infected chicken, Marek’s Disease (MD) is a lymphoproliferative and neuropathic disease of domestic chickens and less commonly of turkeys and quails, caused by a highly contagious, cell-associated, oncogenic herpes virus (Schat and Nair, 2008). Marek’s Disease Virus (MDV) strains that induce disease in chicken are classified as serotype-1 under alpha-herpesvirus. The disease is usually characterized by mononuclear cellular infiltration in peripheral nerves and various other organs and tissues including iris and skin. Marek’s disease virus spreads rapidly throughout flocks by direct  premises, litter, dust and chopped feathers. Most important is the airborne route of infection (Josipovic, 1990). This study was aimed to describe the epidemiology of Marek’s disease based on gross and microscopic lesions, i.e. visceral lymphoma, in seven different native and crossbred chicken strains maintained at University farm in Anand and received for post-mortem in Pathology department over a period of one year.
Keywords: Marek’s disease; Poultry; Visceral lymphomas